Analysis of CSR Models in Improving English Recount Text Reading Skills in Karya Vocational High Schools - Aprillia; Sinta Rukiastiandari; Fara Mutia; Luthfia Rohimah; Endang Sri Andayani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Reading comprehension is one of the essential skills in English language learning at the high school level at Pendidikan Karya Tangerang. Based on initial observations, it was found that reading comprehension skills, especially in recount texts, are still relatively low. This is characterized by difficulties in understanding the main ideas, detailed information, vocabulary, and the sequence of events in the text. This study aims to analyze the application of the Collaborative Strategic Reading (CSR) model in improving reading comprehension skills in English recount texts.This study used a pre-test and post-test control group design. The research sample consisted of 60 eleventh-grade students, divided into two groups: an experimental group (30 students) taught using the CSR model and a control group (30 students) taught using conventional learning methods. The results of the pre-test and post-test control showed a significant difference in reading comprehension ability between the experimental class (82,40) and the control class (72,10), indicating that the increase in scores in the experimental class was greater than in the control class. The N-Gain score for the experimental class was in the medium-high category (0,54), while the control class (0,28) was in the medium category.These findings indicate that the CSR model is effective in improving students' English recount text reading comprehension skills. This study is expected to serve as a reference for English teachers in implementing innovative and effective collaborative learning models